Mechanical and hydrodynamic swelling characteristics of bovine tanned leather post-treated by acrylic and glutaraldehyde tanning agents - Mondal, A; Chattopadhyay, PK (Bangladesh Journal of Scientific and Industrial Research, 2016)
Chromium tanned cow hides collected at two different stages (i.e. pre-neutralization and pre-finishing) have been treated separately with acrylic and glutaraldehyde based tanning agents. Both mechanical and hydrodynamic swelling properties of these treated samples were investigated. Observed results revealed that overall tensile properties and resistance against hydrodynamic swelling have been improved in all the treated samples as compared to those of untreated samples. Such improvement has been realized through measurement of crosslink densities via fitment of Mooney-Rivlin equation on the tensile plot. Leather post-treated with acrylic copolymer has envisaged superior results as compared to leather post-treated with gluteraldehyde based tanning agent. After one swelling / deswelling cycle, slight material loss has been incurred in all the samples, which is the highest for leather post-treated with glutaraldehyde. Such post-treatment of leather can be a useful measure to enhance the performance properties of leather samples already manufactured in the tannery. Bangladesh J. Sci. Ind. Res. 51(1), 1-12, 2016